Development of A Training Model For CT Scan Equipment To Improve The Competence of Radiographers - Andhika, Adi; Soeprijanto, Soeprijanto; Sugiyanta, Lipur (Politeknik Kesehatan Kemenkes Jakarta II, 2023)
Results of the author’s survey in Radiology Mitra Keluarga Kelapa Gading Hospital, there is a discrepancy between the length of service of employees (Radiographers) and their career level competencies for each year, Radiographers have worked for quite a long time but their skills are still very lacking. Apart from that, the current training unorganized and undirected, giving the impression that it is just plain training. This research aims to carry out development, the development carried out is developing the current CT Scan equipment training into better training capable of increasing the competency of Radiographers at Mitra Keluarga Kelapa Gading Hospital. The development model carried out is using the Dick and Carey model, where the results of this process are a CT Scan training model product called the Kyazeka training model, with the title of the book